Biodegradable Polylactide Nanocapsules Containing Quercetin for In Vitro Suppression of Mouse B16F10 and Human Sk-Mel-28 Melanoma Cell Lines - Chenhui Zhao; Thomas Ming Swi Chang (Pharmaceuticals, 2025)
Background: Quercetin is a flavonoid found in various dietary sources. It is a prodrug converted by overexpressed tyrosinase in melanoma into an active o-quinone that suppresses tumour growth. However, injected quercetin is rapidly cleared from the tumour site. Method: Our study aimed to enhance quercetin’s efficacy through nanoencapsulation using biodegradable nanocapsules, which were tested in both mouse and human melanoma cell lines in 2D and 3D models. Results: Nanoencapsulation achieved sustained release and improved bioavailability. In mouse 2D cultures, quercetin nanocapsules (Q-nanos) reduced cell viability to 28%, compared with 46% for free quercetin (Q-only) (p < 0.05). In 3D cultures simulating in vivo conditions, Q-nanos reduced viability to 43%, showing significant anti-melanoma activity, while Q-only resulted in 72% viability (p > 0.05 vs. control). A similar trend was observed in human melanotic melanoma, where both Q-nanos and Q-only were effective compared with the controls, with Q-nanos demonstrating superior tumour inhibition (p < 0.05). Conclusions: These findings show the superior efficacy of nanoencapsulated quercetin over free quercetin. Nanoencapsulation prolonged quercetin’s bioavailability, enhanced tumour regression, and addressed limitations associated with the rapid clearance of free quercetin.